Agreement between dual-energy x-ray absorptiometry and bioelectric impedance analysis for assessing body composition in athletes: A systematic review and meta-analysis - Dzator, S. B.; Weerasekara, I.; Shields, M. B.; Haslam, R.; James, D. (Clinical Journal of Sport Medicine, 2023)
Objective: To compare dual-energy x-ray absorptiometry (DXA) and bioelectric impedance analysis (BIA) in the assessment of body composition in athletes.